Geographic distribution and new localities for cryptic species of the Aneura pinguis complex and Aneura maxima in Poland - Bączkiewicz, Alina; Gonera, Patrycja; Buczkowska, Katarzyna (Biodiversity: Research and Conservation, 2016)
The genus Aneura is represented in Poland by two species - A. pinguis and A. maxima. A. pinguis in contrast to A. maxima is a complex of cryptic species temporarily named A. pinguis species: A, B, C, and E. All species of the A. pinguis complex and A. maxima differ in their geographic distribution and habitat preferences. A. pinguis species A grows mainly on humus over limestone rocks in the Western Carpathians, A. pinguis species B occurs mainly on clay soil in Bieszczady Mts. and in clayish areas of lowlands, A. pinguis species C grows both in lowlands and mountains and it occupies mostly wet sandy soils, on the shores of oligotrophic lakes and river and mountain stream banks, A. pinguis species E is connected with calcareous rocks in flowing water in mountains. A. maxima grows over the country - both in lowlands and mountains, in marshes situated on the river banks.